Development of android interactive media to improve ethnosocial integrated numeracy literacy - Anastasha, Desty Ayu; Lasari, Yufi Latmini; Safitri, Fazi; Firdausi, Firna Nahwa; Hanafi, Hanafi (Mitra PGMI: Jurnal Kependidikan MI, 2026)
This study aimed to develop an Android-based interactive learning media integrated with ethnosocial values to enhance numeracy literacy among fifth-grade Madrasah Ibtidaiyah students. The study employed a Research and Development approach using the Borg and Gall model, consisting of needs analysis, design, development, and product testing stages. The subjects included fifth-grade students of MIN 1 Sungai Tarab, classroom teachers, and expert validators. Data were collected through interviews, observations, questionnaires, and numeracy literacy tests. Data analysis was conducted using descriptive qualitative and quantitative techniques to assess the validity, practicality, and effectiveness of the developed media. The results showed that the media achieved a validity score of 83%, indicating a highly valid category. Practicality analysis revealed student response scores of 78.8% and teacher response scores of 66%, both categorized as practical. Effectiveness testing demonstrated that students’ numeracy literacy achievement reached a classical mastery level of 85.6%. These findings indicate that the developed Android-based interactive learning media meets the criteria of validity, practicality, and effectiveness for use in numeracy learning at the Madrasah Ibtidaiyah level.